PEMBELAJARAN SEJARAH DENGAN METODE DEBAT AKTIF UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Rakhman, Akhmad; Handayani, Yeni; Bakhtiar, Ahmad (Jurnal Lingkar Mutu Pendidikan, 2025)
The aim of this reseacrh is to find out history learning using the active debate method to increase students interest in learning in class x SMA Budhi Warman I. This research was conducted using a qualitative descripstive method. This research technique uses observation, interview and documentation. The results of this reseacrh show that it has a positive effect in increasing students interest in learning compared to using the lecture method. Apart from that, the application of this active debate method can train students to make strong arguments in solving controversial problens and to have a democratic attitude and respect each othe for different opinions.